2018
DOI: 10.3390/nu10091194
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Human Milk Composition: The Role of Infant Sex in Determining Early Life Nutrition

Abstract: Male and female infants respond differentially to environmental stimuli, with different growth and neurodevelopmental trajectories. Male infants are more likely to be disadvantaged when subjected to adversity and show a higher risk of perinatal complications. However, the underlying causes of this sex-bias are not well defined and optimising the early life nutritional care may be necessary to minimise the “male disadvantage” that may be experienced early in life. Experimental models have demonstrated that anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 61 publications
4
71
0
1
Order By: Relevance
“…Conversely, among males, growth was not predicted by cortisol but rather positively predicted by DHEAS concentrations at early lactation and by increases in milk DHEAS concentrations from early to peak and peak to late lactation. These results contribute to the growing body of evidence for sex‐differentiated mechanisms underlying physiological processes during early development in other animals (Badyaev, ; Brummelte, Lieblich, & Galea, ; Carpenter, Grecian, & Reynolds, ; Galante et al, ). For example, among rhesus macaques in this population, the quantity and quality of milk differs by offspring sex (Hinde, ), and male and female offspring differ in sensitivity to maternal milk cortisol in relation to temperament (Hinde et al, ).…”
Section: Discussionsupporting
confidence: 59%
“…Conversely, among males, growth was not predicted by cortisol but rather positively predicted by DHEAS concentrations at early lactation and by increases in milk DHEAS concentrations from early to peak and peak to late lactation. These results contribute to the growing body of evidence for sex‐differentiated mechanisms underlying physiological processes during early development in other animals (Badyaev, ; Brummelte, Lieblich, & Galea, ; Carpenter, Grecian, & Reynolds, ; Galante et al, ). For example, among rhesus macaques in this population, the quantity and quality of milk differs by offspring sex (Hinde, ), and male and female offspring differ in sensitivity to maternal milk cortisol in relation to temperament (Hinde et al, ).…”
Section: Discussionsupporting
confidence: 59%
“…In secretors, mothers of boys had higher concentrations of LNFP-I, LNH, LNnH, IFLNH-I, IFLNH-III and DFLNH-a&c than those of girls. The difference in perinatal outcomes between males and females has been recognized as the "male disadvantage" since the 1970s [49]. Boys may need more HMOs than girls, and this theory needs further studies.…”
Section: Other Factors and Hmosmentioning
confidence: 99%
“…Extensive evidence from animal models has shown that these compounds are likely to be active in HM and, once ingested by the infant, exert a range of physiological functions [5]. Changes in HM nutritional and hormonal composition have been well documented throughout the sequential stages of lactation [6,7], per feed [8], per day [9], across mothers with different phenotypic characteristics [10,11], socioeconomic status [12] and infants of different sex [13]. Limited studies to date [11,[14][15][16][17] have reported alterations in the HM bioactive, amino and fatty acid profiles of women with gestational diabetes mellitus (GDM) or elevated body mass index (BMI), suggesting that HM may have different nutritional and hormonal composition associated with individual maternal characteristics.…”
Section: Introductionmentioning
confidence: 99%